The evolution of the histone methyltransferase gene Su(var)3-9 in metazoans includes a fusion with and a re-fission from a functionally unrelated gene. - Krauss, V.; Fassl, A.; Fiebig, P.; Patties, I.; Sass, H. (BMC Evolutionary Biology, 2006)
In eukaryotes, histone H3 lysine 9 (H3K9) methylation is a common mechanism involved in gene silencing and the establishment of heterochromatin. The loci of the major heterochromatic H3K9 methyltransferase Su(var)3-9 and the functionally unrelated gamma subunit of the translation initiation factor eIF2 are fused in Drosophila melanogaster. Here we examined the phylogenetic distribution of this unusual gene fusion and the molecular evolution of the H3K9 HMTase Su(var)3-9.We show that the gene fusion had taken place in the ancestral line of winged insects and silverfishs (Dicondylia) about 400 million years ago. We cloned Su(var)3-9 genes from a collembolan and a spider where both genes ancestrally exist as independent transcription units. In contrast, we found a Su(var)3-9-specific exon inside the conserved intron position 81-1 of the eIF2gamma gene structure in species of eight different insect orders. Intriguinly, in the pea aphid Acyrthosiphon pisum, we detected only sequence remains of this Su(var)3-9 exon in the eIF2gamma intron, along with an eIF2gamma-independent Su(var)3-9 gene. This reveals an evolutionary re-fission of both genes in aphids. Su(var)3-9 chromo domains are similar to HP1 chromo domains, which points to a potential binding activity to methylated K9 of histone H3. SET domain comparisons suggest a weaker methyltransferase activity of Su(var)3-9 in comparison to other H3K9 HMTases. Astonishingly, 11 of 19 previously described, deleterious amino acid substitutions found in Drosophila Su(var)3-9 are seemingly compensable through accompanying substitutions during evolution.Examination of the Su(var)3-9 evolution revealed strong evidence for the establishment of the Su(var)3-9/eIF2gamma gene fusion in an ancestor of dicondylic insects and a re-fission of this fusion during the evolution of aphids. Our comparison of 65 selected chromo domains and 93 selected SET domains from Su(var)3-9 and related proteins offers functional predictions concerning both domains in Su(var)3-9 proteins.